The chalk artist : a novel - Goodman, Allegra (The Dial Press, 2017)
Collin James is young, creative, and unhappy. A college dropout, he waits tables and spends his free time beautifying the streets of Cambridge, Massachusetts, with his medium of choice: chalk. Collin's art captivates passersby with its vibrant colors and intricate lines--until the moment he wipes it all away. Nothing in Collin's life is meant to last. Then he meets Nina. . . . The daughter of a tech mogul who is revolutionizing virtual reality, Nina Lazare is trying to give back as a high school teacher--but her students won't listen to her. When Collin enters her world, he inspires her to think bigger. Nina wants to return the favor--even if it means losing him. Against this poignant backdrop, Allegra Goodman paints a tableau of students, neighbors, and colleagues: Diana, a teenage girl trying to make herself invisible; her twin brother, Aidan, who's addicted to the games produced by Nina's father; and Daphne, a viral-marketing trickster who unites them all, for better or worse.